Factors Influencing MIS Design in Small and Medium Sized Organization: Jordanian Perspective - Mustafa, Saed Adnan (2009)
With the advent of the technological revolution, economic globalization and the fundamental change of the social production method, human capital and social capital have become the key factors for business organization to achieve competitive advantage(Li and Hu, 2007). Management information system (MIS) is a system that provides the necessary information to manage an organization effectively. MIS and the information it generates are generally considered essential components of prudent and reasonable business decisions (Comptroller of the Currency Administrator of US National Banks, 1995). The study conducted on SME’s in Jordan to identify the factors that affect the adoption of MIS among these organizations. The results of the survey provide perspectives that have primarily not been explored in Jordanian organization.In assessing factors influencing MIS design for small and medium sized organizations(Cornbach Alpha=0.893) developed by Campion (1988) we adopted them in the pilottest and used in the research. In describing factors influencing MIS design for small and medium sized organizations in Jordan were taken for this purpose of this study.Statistical analysis used were frequency counts, percentages, means, ANOVA, Person’s,Multiple Regression Analysis and Liner correlation. Analysis was set at 0.05 level of significant using SPSS (Version 12.0) computer software.Overall, the respondents “agreed” on the factors influencing MIS design for small and medium sized organizations